2019
DOI: 10.1186/s12864-019-6175-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the fecal microbiota of fast- and slow-growing rainbow trout (Oncorhynchus mykiss)

Abstract: BackgroundDiverse microbial communities colonizing the intestine of fish contribute to their growth, digestion, nutrition, and immune function. We hypothesized that fecal samples representing the gut microbiota of rainbow trout could be associated with differential growth rates observed in fish breeding programs. If true, harnessing the functionality of this microbiota can improve the profitability of aquaculture. The first objective of this study was to test this hypothesis if gut microbiota is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 48 publications
5
26
1
Order By: Relevance
“…Similarly, studies in stickleback fish identified association between gut microbial differences and host genetic divergence [24]. Besides, previous work from our lab group revealed significant variation in beta diversity of the bacterial communities of rainbow trout families showing variation in growth rate [25]. Together, these studies indicate a substantial impact of host selection or genetics in predicting the hostassociated microbial assemblages.…”
Section: Comparison Of Gut Assemblages In High-and Low-muscle Yield Gsupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, studies in stickleback fish identified association between gut microbial differences and host genetic divergence [24]. Besides, previous work from our lab group revealed significant variation in beta diversity of the bacterial communities of rainbow trout families showing variation in growth rate [25]. Together, these studies indicate a substantial impact of host selection or genetics in predicting the hostassociated microbial assemblages.…”
Section: Comparison Of Gut Assemblages In High-and Low-muscle Yield Gsupporting
confidence: 59%
“…To extract DNA, fecal samples from 19 ARS-FY-H and 20 ARS-FY-L fish were subjected to DNA isolation using a Promega Maxwell DNA Isolation Kit (Promega Corporation, Madison, WI), as we previously described [25] with a minor modification where 20 µL of lysozyme was added in samples to facilitate cell wall lysis. Briefly, 200 mg of fecal sample was added to a microtube containing 160 µL of incubation buffer, 20 µL proteinase k solution, and 20 µL lysozyme.…”
Section: Dna Extraction Library Preparation and Sequencingmentioning
confidence: 99%
“…Burkholderiaceae, Lachnospiraceae, Ruminococcaceae, and Paenibacillaceae were also enriched in A. digitifera fragments subjected to ALAN. It is worth noting that these microbial taxa are major taxonomic groups found in the human gut and in fecal microbiota [ 65 , 66 , 67 , 68 , 69 ], as well as in the fish gut microbiome [ 70 , 71 ]. The milkfish aquaculture zone and human settlements found in proximity to the Bolinao Marine Laboratory [ 72 ] are possible sources of these bacterial groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in stickleback sh identi ed an association between gut microbial differences and host genetic divergence [24]. Previous work from our lab group revealed signi cant variation in beta diversity of the bacterial communities of rainbow trout families showing variation in growth rate [25]. Together, these studies indicate a substantial impact of host selection or genetics in predicting host-associated microbial assemblages.…”
Section: Comparison Of Gut Assemblages In High-(ars-fy-h) and Low-(armentioning
confidence: 59%
“…To extract DNA, fecal samples from 19 high (ARS-FY-H) and 20 low (ARS-FY-L) genetic line sh were subjected to DNA isolation using a Promega Maxwell DNA Isolation Kit (Promega Corporation, Madison, WI), as we previously described [25] with a minor modi cation where 20 μL of lysozyme was added in samples to facilitate cell wall lysis. Brie y, 200 mg of fecal sample was added to a microtube containing 160 μL of incubation buffer, 20 μL proteinase k solution, and 20 μL lysozyme.…”
Section: Dna Extraction Library Preparation and Sequencingmentioning
confidence: 99%